Arabic sociolinguistics - Bassiouney, Reem, 1973- (Edinburgh University Press, 2009)
The first introduction to the field of Arabic sociolinguistics, this book discusses major trends in research on diglossia, code-switching, gendered discourse, language variation and change, and language policies in relation to Arabic. In doing so, it introduces and evaluates the various theoretical approaches, and illustrates the usefulness and the limitations of these approaches with empirical data. The book shows how sociolinguistic theories can be applied to Arabic and, conversely, what the study of Arabic can contribute to our understanding of the function of language in society. Key Features Introduces current theories and methods of sociolinguistics, with a special focus on Arabic. Topics include: language variation and change, gender, religion and politics. Aimed at students and scholars of Arabic with an interest in linguistics and students and scholars of linguistics with an interest in Arabic.